Comparison of ion channel inhibitor combinations for limiting secondary degeneration following partial optic nerve transection - Toomey, L.; Bartlett, C.; Majimbi, Maimuna; Gopalasingam, G.; Rodger, J.; Fitzgerald, Melinda (Springer, 2018)
Following neurotrauma, secondary degeneration of neurons and glia adjacent to the injury leads to further functional loss. A combination of ion channel inhibitors (lomerizine + oxATP + YM872) has been shown to be effective at limiting structural and functional loss due to secondary degeneration. Here we assess efficacy of the combination where oxATP is replaced with Brilliant Blue G (BBG), a more clinically applicable P2X7 receptor inhibitor. Partial optic nerve transection was used to model secondary degeneration in adult female rats. Animals were treated with combinations of lomerizine + YM872 + oxATP or lomerizine + YM872 + BBG, delivered via osmotic mini-pump directly to the injury site. Outcomes assessed were Iba1 + and ED1 + microglia and macrophages, oligodendroglial cell numbers, node/paranode structure and visual function using the optokinetic nystagmus test. The lomerizine + BBG + YM872 combination was at least as effective at the tested concentrations as the lomerizine + oxATP + YM872 combination at preserving node/paranode structure and visual function when delivered locally. However, neither ion channel inhibitor combination significantly improved microglial/macrophage nor oligodendroglial numbers compared to vehicle-treated controls. In conclusion, a locally delivered combination of ion channel inhibitors incorporating lomerizine + BBG + YM872 is at least as effective at limiting secondary degeneration following partial injury to the optic nerve as the combination incorporating oxATP.